Numerical Simulation of Support Design Using Rock Bolt in Bord and Pillar Method - Hasim, Rizwan (IIT (BHU), Varanasi, 2020)
The trend of Indian underground coal mines is going into mechanization by adopting continuous miner technology in Bord and Pillar's work. The machine has operated in a wider gallery size of up to 6.6 m for the smooth maneuvering of the machine and fast retreating during the depilating stage. The conventional method of mining using Load Haul Dumper (LHD)/ Side Discharge Loader (SDL) machine requires gallery sizes up to 4.8 m. One of the roof support design is established on empirical expression based on the geo-mechanical classification of the roof. Various researchers proposed the geo-mechanical classification of roofs (Terzagi, 1946, Bieiawski, 1989, 1976 Barton et al., 1974). CMRI-ISM RMR (Venkatesvarlu et al., 1989) proposed the geo-mechanical classification of roofs based on statistical analysis for various underground coal mines in India. The applicability of any empirical approach is limited within the range of the dataset. Full abstract is available in the attachment.
This thesis was submitted by Rizwan Hasim Roll No. 14151008 Department of Mining Engineering IIT (BHU) IIT (BHU) Varanasi – 221005 Supervised by Prof. B. K. Shrivastva and Dr. Ashok Jaiswal
Keywords: Rock Bolt; Simulation